A distância entre a pena e o discurso : a narrativa das cartas ânuas na província jesuítica do Paraguai no século XVII (1609-1615) - Barbosa, Déborah da Costa Ribeiro (2024)
The production of narratives about America was one of the mechanisms employed in the colonial project of conquering the continent. Within this colonial project, the Jesuit missionaries operated in the territory and produced an extensive body of documents. Developed shortly after the arrival of the first Europeans in America, the Society of Jesus used writing as a tool for decision making and control within the Order, which had members in diferente regions. The creation of an “other” this writing involves various layers and complexities. In the epistolary writing prescribed by the guidelines of the Society of Jesus, different subjective and experiences also a play role in shaping this “other”. By questioning the construction and narrative framing of the Amerindian populations inhabiting the territory later defined as the Jesui Province of Paraguay from 1609 to 1615, examining the diverse ways the Company’s intentions and representation of the natives were portrayed. The aim is to comprehend the process of discursive composition in those early Annual Letters, considering their production and reception context, as well as the potential impact of various understanding and logics.